TRIPLE NEGATIVE BREAST CANCER AND DRUG-RESISTANT CELLS - Atakhanova N.E (Scholar Express Journals, 2023)
The triple negative breast cancer (TNBC) subtype is known to have a more aggressive clinical course compared to other breast cancer subtypes. Targeted therapy for this type of breast cancer is limited, and patients are primarily treated with conventional chemotherapy and radiotherapies, which are not specific and do not target resistant cells. Thus, one of the major clinical challenges is to find compounds that target drug-resistant cell populations responsible for the transformation of secondary tumors. Molecular profiling of different TNBC subtypes offers hope for better identifying these tumor-specific resistant cells. To this end, a better understanding of TNBC heterogeneity and cancer stemness is required . and extensive genomic analysis can help understand the complexity of the disease and highlight new molecular drivers that can be targeted in the clinic. The use of therapies targeting persistent cancer cells in combination with other treatments may provide major advances in improving survival for patients with TNBC
Keywords: treatments; secondary; cells; targeted